A single point mutation in the envelope gene is responsible for replication and XC fusion deficiency of the endogenous ecotropic C3H/He murine leukemia virus and for its repair in culture. - Sithanandam, G (1988)
The molecular basis has been determined for differences in infectivity and XC phenotype of endogenous ecotropic murine leukemia virus of the low-leukemia mouse strain C3H/He, its relative in the high-leukemia mouse strain AKR, and highly infectious, XC-positive C3H virus variants selected in vitro. Endogenous ecotropic type C virus induced by iododeoxyuridine from the nontransformed C3H/10T1/2 cell line is XC negative and replication deficient. In contrast, viruses produced late after iododeoxyuridine induction in chemically transformed C3H/10T1/2 cells (MCA5) are XC positive and infectious. XC-negative viruses can be converted to XC-positive viruses by being grown in certain transformed cell lines. We have cloned the endogenous ecotropic provirus of C3H/He from MCA5 cells, which is XC negative and replication deficient, as well as two XC-positive C3H proviruses derived by in vitro conversion. Fragment exchange between the XC-negative molecular clone p110 and the XC-positive AKR virus clone p623 revealed that the defect in p110 lies 3' of the SalI site located in the pol region. Nucleotide sequencing established that the C3H p110 provirus was integrated within the R region of an endogenous VL30 long terminal repeat (LTR) in reverse orientation and that the virus differed from the infectious AKR p623 provirus by a point mutation, substituting Lys for Arg at the potential precursor cleavage site for gp70 and p15E. In vitro-converted XC-positive C3H proviral clones 3211 and 4211 are identical to XC-negative C3H p110, except that they have Arg at this site and the normal cleavage site is thus regenerated in these clones. The XC-negative C3H p110 was blocked in processing of Pr85env, whereas clones 3211 and 4211 had normal cleavage of the env precursor into gp70. Both the XC-negative C3H provirus and the in vitro-converted XC-positive C3H proviruses had a single copy of a 99-base-pair enhancer element in the LTR, whereas two copies of this sequence are present in the AKR proviral LTR. Substitution of Arg for Lys at the envelope precursor processing site of C3H p110 by site-directed mutagenesis is sufficient by itself to convert the virus to the XC-positive replication-competent phenotype. Thus, we have established that a single point mutation at the processing site of the envelope precursor protein Pr85 is responsible for the difference in the infectivity and XC phenotype of endogenous ecotropic murine leukemia virus from C3H/He and AKR mice and that the basis for in vitro conversion is a mutation at this site.